2021
DOI: 10.15587/1729-4061.2021.239255
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of intercity bus public transport safety perception modeling using conjoint

Abstract: Public transport safety is still an issue that needs to be studied by bureaucrats and researchers. This is because public bus accidents are still quite high. This is because many families, involved in traffic accidents, are shocked by the accident. Therefore, the problem of perception of a safe bus needs to be studied. The purpose of this study was to determine the perception model of a safe public bus. Mathematical modeling based on the parameters that have been studied was selected first. While the second ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Road transportation safety modeling has been made using a conjoint analysis approach. The research was applied to intercity bus public transport safety perception modeling [25]. Meanwhile, research on the effect of geometric parameters associated with the promotion and reduction of accidents can serve as an accident prevention measure.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Road transportation safety modeling has been made using a conjoint analysis approach. The research was applied to intercity bus public transport safety perception modeling [25]. Meanwhile, research on the effect of geometric parameters associated with the promotion and reduction of accidents can serve as an accident prevention measure.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…According to the National Police, the highest number of accidents in Indonesia occurred in 2019, with 116,441 fatalities. Several previous studies have found that the human factor is the main cause of accidents [6,7]. This study examines in depth the driver factors of several variables, namely socio-economic and travel patterns, completeness and preparation for driving, driving habits, driving behavior, and the chance of an accident.…”
Section: Introductionmentioning
confidence: 99%
“…Humans are the factor that has the most role in causing traffic accidents, and three factors that greatly affect aspects of driving safety are human characteristics as drivers, human habits while driving, and human behavior while driving [5]. Analysis by [6] revealed that driving behavior increases the risk of having an accident by 50 %. According to the National Police, the highest number of accidents in Indonesia occurred in 2019, with 116,441 fatalities.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Indonesian National Police, the highest number of accidents in Indonesia occurred in 2019, with 116,441 casualties. Previous studies have found that the human factor is the leading cause of accidents [4,5]. Research has shown that driving behavior has a positive and significant relationship with accident involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that driving behavior has a positive and significant relationship with accident involvement. Analysis by [5] revealed that driving behavior increases the risk of 50 % of having an accident. The most important part of accident involvement [6,7].…”
Section: Introductionmentioning
confidence: 99%